PHOSPHODIESTERASE 5 ACTIVITY INHIBITING COMPOSITION - HASEGAWA SHINYA; TACHIKI KENSUKE; AKAGI JUNJI (2021)
To provide a new composition that can inhibit activity of PDE5. A phosphodiesterase 5 activity inhibiting composition contains a processed product of at least one plant selected from a group consisting of Filipendula, Myrica, Eugenia, Lagerstroemia, Terminalia, Haematoxylon and Uncaria. 本发明的目的在于提供一种能够抑制PDE5活性的新的组合物。一种5型磷酸二酯酶活性抑制用组合物，其含有选自蚊子草属(Filipendula)、杨梅属(Myrica)、番樱桃属(Eugenia)、紫薇属(Lagerstroemia)、榄仁树属(Terminalia)、采木属(Haematoxylon)和钩藤属(Uncaria)中的至少1种植物的加工物。